Reciprocity and matching frictions - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
We build a RBC endogenous separation matching model and introduce efficiency wages along the lines of Akerlof (1982). While the standard endogenous separation matching model reveals shortcomings in explaining correlations and volatilities jointly, this approach performs reasonably well along both dimensions. The proper introduction of real rigidities can consistently enhance the performance of the (endogenous separation) matching model.
Keywords: E32; J41; J64; 330; Efficiency Wages; Endogenous Separations; Search and Matching